Acetate-Induced Milk Fat Synthesis Is Associated with Activation of the mTOR Signaling Pathway in Bovine Mammary Epithelial Cells - Miao Lin; Maocheng Jiang; Tianyu Yang; Dejin Tan; Guanghui Hu; Guoqi Zhao; Kang Zhan (Animals, 2022)
Acetate is a precursor substance for fatty acid synthesis in bovine mammary epithelial cells (BMECs), and the mTOR signaling pathway plays an important role in milk fat synthesis. However, the mechanism of the regulatory effects of acetate on lipogenic genes via the mTOR signaling pathway in BMEC remains unknown. We hypothesized that acetate can enhance the expression of lipogenic genes and triglyceride (TG) production by activating the mTOR signaling pathway in BMECs. Therefore, the aim of this study was to investigate the network of acetate-regulated lipid metabolism by the mTOR signaling pathway in BMECs. These results showed that TG synthesis was elevated (p < 0.01) in BMECs with acetate treatment. The lipid droplets were increased in the acetate-treated groups compared with those in the control group through the Bodipy staining of the lipids. In addition, the fatty acid profile in BMECs treated with acetate was affected, with an elevation in the proportions of C14:0, C16:0, and C18:0. The mRNA levels of the sterol-response-element-binding protein 1 (SREBP1), stearoyl-CoA desaturase 1 (SCD1), and fatty acid synthase (FAS) genes involved in the lipogenesis and transcriptional factors were upregulated (p < 0.05) in BMECs with acetate treatment. Remarkably, the expression of acetyl-CoA carboxylase α (ACCα) and FAS rate-limiting enzymes involved in lipogenesis was upregulated in BMECs with acetate treatment. Moreover, the addition of acetate enhanced the key protein expression of S6K1, which is related to the mTOR signaling pathway. Taken together, our data suggest that TG accumulation and expression of lipogenic genes induced by acetate are associated with the activation of the mTOR signaling pathway, which provides new insights into the understanding of the molecular mechanism in the expression of mTOR-signaling-pathway-regulated lipogenic genes.